Analysis of Liquidity, Profitability and Solvency Ratios to Assess the Financial Performance of Companies in Cigarette Industries Listed on the Indonesia Stock Exchange - Andy Andy; Melly Megawati (Komunitas Dosen Indonesia, 2019)
The writing of this reaserch is aimed at knowing the company's financial performance which is assessed through ratio analysis, namely liquidity ratio, profitability and solvency. The research conducted is to analyze the company's financial statements, namely the income statement, statement of financial position or balance sheet, while for the research method carried out is to use descriptive methods. By analyzing the company's financial statements are expected to be able to provide an overview of the financial condition of the company. Based on the results of the analysis and discussion, it can be concluded that the company's performance is still not all stable. This is due to policies regarding the sale and marketing of cigarettes in Indonesia. The results of the study show that PT. Gudang Garam Tbk is a company that does not experience much increase or decrease until it can be said that the company is safe. PT. Handjaya Mandala Sampoerna Tbk is a company that has the highest profit compared to 3 (three) other companies. PT. Bentoel International Investama Tbk suffered losses throughout 2013 to 2015. Meanwhile, PT. Wismilak Inti Makmur Tbk is in good condition as seen from the Liquidity Ratio. PT. Wismilak Inti Makmur Tbk is the most stable company and is able to manage its finances well even though the company has the lowest assets compared to 3 (three) other companies